Exegetical Puzzles and the Mystical Theologies of Gregory of Nyssa and Dionysius the Areopagite - Conway-Jones, Ann (Vigiliae Christianae, 2021)
Abstract Gregory of Nyssa and Dionysius the Areopagite both contemplate the Exodus narrative of Moses’ experiences on Sinai. That narrative is complex, with Moses ascending and descending the mountain several times, sometimes in company, sometimes alone. Gregory follows the biblical twists and turns in Life of Moses ; the relevant paragraph in Dionysius’ Mystical Theology tells of just one ascent. This article re-examines their dependence on the details of the biblical text, arguing that its exegetical puzzles proved fertile ground for their apophatic insights. Both seize on Exodus 20:21 as symbolising the utter incomprehensibility of God. But they resolve the enigmas of Exodus 33–34 differently. Gregory uses Exodus 33:18–23 as a springboard to his articulation of a never-ending journey into the infinite divine, while Exodus 34:29–35 provides the biblical impetus behind Dionysius’ concept of “union.”